Green synthesis of sulfur nanoparticles using Melissa officinalis leaves and its effect on powdery mildew (Erysiphe necator Schw.) in vineyard - Orhan, Ramazan; Ozgen, Inanc; Turkolmez, Sahimerdan; Aydogmus, Ercan; Turan, Mehmet Deniz; Erzen, Buket; Rastgeldi, Ismail (Gazi Univ, Fac Engineering Architecture, 2025)
One of the fungal diseases that causes significant product and quality losses in viticulture all over the world and in our country is powdery mildew caused by Erysiphe necator Schw.. The disease negatively affects grape cluster quality and yield under hot and dry weather conditions. Powdered sulfur is generally used in the fight against this disease, but most of the time, phytotoxicity occurs in the plant due to the use of sulfur. Nowadays, nanoparticles have attracted considerable attention because of their different physicochemical properties. Nanoparticles are used in fungicides, bactericides, and nanofertilizers because of their small size, large surface area, and high reactivity. It is quite important to produce nanomaterials using sustainable and eco-friendly methods. Among these methods, the green synthesis method is the most suitable because of its simplicity, ease of use, environmental friendliness, excellent biocompatibility, and low biotoxicity. In the current study, nanosulfur was synthesized using melissa leaf (Melissa officinalis L.), which is known for its high polyphenol content and easy availability. The effective formation of synthesized SNPs was examined by UV-Visible spectroscopy, XRD, FTIR, FE-SEM, EDX, TEM, particle size analysis, and zeta potential analyses. The average particle size was determined to be between 21.4 and 126.8 nm. The synthesized nanosulfur was applied to grapevines in the vineyard to determine its effect against grapevine powdery mildew (Erysiphe necator Schw.) disease and then compared with powdered sulfur. It was determined that nanosulfur application was 79.21% effective and powdered sulfur application was 68.28% effective in preventing grapevine powdery mildew disease.
Melissa officinalis yaprakları kullanılarak kükürt nanopartiküllerinin yeşil sentezi ve üzüm bağlarında külleme (Erysiphe necator Schw.) üzerindeki etkisi
Keywords: Green synthesis; nanosulfur; melissa leaf; powdery mildew